Guidelines for preparation and flow cytometry analysis of human nonlymphoid tissue DC - Dudziak, Diana; Heger, Lukas; Agace, William W; Bakker, Joyce; Gruijl, Tanja D.; Dress, Regine J.; Dutertre, Charles‐Antoine; Fenton, Thomas M.; Fransen, Marieke F.; Ginhoux, Florent; Heyman, Oded; Horev, Yael; et al. (European journal of immunology, 2025)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state‐of‐the‐art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs, and various nonlymphoid tissues. Within this article, detailed protocols are presented that allow for the generation of single‐cell suspensions from human nonlymphoid tissues including lung, skin, gingiva, intestine as well as from tumors and tumor‐draining lymph nodes with a subsequent analysis of dendritic cells by flow cytometry. Further, prepared single‐cell suspensions can be subjected to other applications including cellular enrichment procedures, RNA sequencing, functional assays, etc. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer‐reviewed by leading experts and approved by all co‐authors, making it an essential resource for basic and clinical DC immunologists. We here provide detailed protocols for isolating single cell suspension from human nonlymphoid tissues, such as gingiva, lung, intestine, skin, and different tumor tissues as well as tumor‐draining lymph nodes. Further, we provide gating strategies for flow cytometric analysis of human DC subpopulations in diverse nonlymphoid tissues.